Baseline Hypothalamic–Pituitary–Adrenal Axis and Parasympathetic Nervous System Activity Interact to Predict Executive Functions in Low‐Income Children. Issue 1 (3rd November 2020) - Braren, Stephen H.; Brandes‐Aitken, Annie; Perry, Rosemarie E.; Williams, Kevon; Lyons, Krystalle; Rowe‐Harriott, Sashana; Blair, Clancy
ABSTRACT: We examined interactions between baseline hypothalamic–pituitary–adrenal (HPA) axis and parasympathetic nervous system (PNS) activity in relation to executive functions (EF) in a sample ( n  = 1, 005) of children in low wealth, nonurban communities at age 48 months. Salivary cortisol and respiratory sinus arrhythmia (RSA) represented baseline HPA axis and PNS activity, respectively. The interaction between RSA and cortisol predicted EF such that children with either lower RSA and lower cortisol, or higher RSA and higher cortisol had higher EF scores. These findings suggest a potential compensatory relation in which the PNS and HPA axis counterbalance each other to support cognition. Abstract : Lay abstract: We investigated whether activity of the two main stress physiology systems, the autonomic nervous system (ANS) and the hypothalamic‐pituitary‐adrenal (HPA) axis, related to children's cognitive performance. Our results indicated that there was an interaction between the HPA axis and ANS in relation to better cognitive performance. These findings suggest that each stress physiology system may flexibly compensate for the other to support children's cognition.